2012
DOI: 10.4314/ajtcam.v9i2.12
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity and Vascular Properties of Seed of Parkia Biglobosa (Jacq) R. Br Gift (Mimosaceae) on Rat Aorta

Abstract: The authors report here the results of study on Parkia biglobosa seeds used in Burkina Faso for arterial hypertension treatment. Investigations were done on acute toxicity and vascular properties of fermented and roasted seeds. Acute toxicity test using mice, revealed by the intraperitoneal route a lethal dose 50 (LD 50 ) of 1800 mg/kg and 1600 mg/kg of body weight for aqueous extract from roasted and fermented seeds respectively. According to the scale of Hodge and Sterner and that of the World Health Organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 6 publications
1
17
1
Order By: Relevance
“…These plants can be developed into alternative medicines for the management of hypertension. The literature search revealed that a number of these plant species are multipurpose plants that are used simultaneously for the treatment of several other diseases [18,28,33,34,38,40,43,45]. Similar to the New World findings [11], these herbs (47%) were mostly sold in the form of leaves, followed by roots (20%), seed (20%) and stem bark (13%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These plants can be developed into alternative medicines for the management of hypertension. The literature search revealed that a number of these plant species are multipurpose plants that are used simultaneously for the treatment of several other diseases [18,28,33,34,38,40,43,45]. Similar to the New World findings [11], these herbs (47%) were mostly sold in the form of leaves, followed by roots (20%), seed (20%) and stem bark (13%).…”
Section: Discussionmentioning
confidence: 99%
“…Documented phytochemical properties Documented antihypertensive activity tannins, coumarins, anthocyanosides and flavonosides are present in both bark and leaf but in different concentrations [33]. treatment of hypertension [33,34].…”
Section: Plant Speciesmentioning
confidence: 99%
“…of the Fabaceae family is one of the important woody forest tree legumes in the semi-arid and sub-tropical farming systems of West Africa [5]. It is a perennial multi-purpose tree species widely used for food, medicine and ecological purposes [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The pods containing-seeds are highly nutritious and rich in protein [6][7][8]. Locally, the seeds are prepared as spicy food/condiments and consumed in soups in many African households [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation